2018
DOI: 10.1159/000493502
|View full text |Cite
|
Sign up to set email alerts
|

miR-26a/HOXC9 Dysregulation Promotes Metastasis and Stem Cell-Like Phenotype of Gastric Cancer

Abstract: Background/Aims: Previous studies demonstrated that HOXC9 acts as an oncogene in several tumors. The aim of this study was to explore whether HOXC9 promotes gastric cancer (GC) progression and elucidate the underlying molecular mechanisms. Methods: HOXC9 expression in GC tissues and adjacent non-cancer tissues was detected by quantitative RT-PCR (qRT-PCR) and immunohistochemistry. The functional effects of HOXC9 on proliferation, metastasis and stem cell-like phenotype were evaluated by relevant experiments in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 22 publications
0
17
0
Order By: Relevance
“…In the present study, lower miR-26a expression was significantly associated with diffuse type GC, but the relationship between miR-26a and Lauren's classification is controversial. While higher miR-26a expression was reported to be associated with diffuse type GCs 35 , others reported downregulated miR-26a in poorly differentiated GCs 36 . More research is needed to clarify how miRNA functions in tumorigenesis according to Lauren's classification.…”
Section: Discussionmentioning
confidence: 95%
“…In the present study, lower miR-26a expression was significantly associated with diffuse type GC, but the relationship between miR-26a and Lauren's classification is controversial. While higher miR-26a expression was reported to be associated with diffuse type GCs 35 , others reported downregulated miR-26a in poorly differentiated GCs 36 . More research is needed to clarify how miRNA functions in tumorigenesis according to Lauren's classification.…”
Section: Discussionmentioning
confidence: 95%
“…The miR-182/HOXA9 axis is implicated in RUNX3-mediated GC development [51]. In addition, HOXC9 contributes to GC progression by inducing EMT, MMP2 expression, and stem cell-like properties [29]. HOXC10 activates ATM/NF-kB pathway and MAPK signalling, functioning as an oncogene in GC [30,54].…”
Section: Mechanisms By Which Hox Proteins Regulate Gcmentioning
confidence: 99%
“…MicroRNAs (miRNAs/miRs) can function as oncogenes or tumor suppressor genes, and regulate gene expression through translational repression or mRNA degradation by binding to the 3'-untranslated region (3'UTR) of their target mRNAs (5,6). Previous studies have identified that miRNAs exhibit aberrant expression and serve essential roles in GC (7)(8)(9)(10). Therefore, further investigation into the expression and function of miRNAs may improve understanding of the molecular mechanisms responsible for the pathogenesis of GC.…”
Section: Introductionmentioning
confidence: 99%